An overview of genes and mutations associated with Chlamydiae species' resistance to antibiotics - Ichrak Benamri; Maryame Azzouzi; Kholoud Sanak; Ahmed Moussa; Fouzia Radouani (BMC, 2021)
Abstract Background Chlamydiae are intracellular bacteria that cause various severe diseases in humans and animals. The common treatment for chlamydia infections are antibiotics. However, when antibiotics are misused (overuse or self-medication), this may lead to resistance of a number of chlamydia species, causing a real public health problem worldwide. Materials and methods In the present work, a comprehensive literature search was conducted in the following databases: PubMed, Google Scholar, Cochrane Library, Science direct and Web of Science. The primary purpose is to analyse a set of data describing the genes and mutations involved in Chlamydiae resistance to antibiotic mechanisms. In addition, we proceeded to a filtration process among 704 retrieved articles, then finished by focusing on 24 studies to extract data that met our requirements. Results The present study revealed that Chlamydia trachomatis may develop resistance to macrolides via mutations in the 23S rRNA, rplD, rplV genes, to rifamycins via mutations in the rpoB gene, to fluoroquinolones via mutations in the gyrA, parC and ygeD genes, to tetracyclines via mutations in the rpoB gene, to fosfomycin via mutations in the murA gene, to MDQA via mutations in the secY gene. Whereas, Chlamydia pneumoniae may develop resistance to rifamycins via mutations in the rpoB gene, to fluoroquinolones via mutations in the gyrA gene. Furthermore, the extracted data revealed that Chlamydia psittaci may develop resistance to aminoglycosides via mutations in the 16S rRNA and rpoB genes, to macrolides via mutations in the 23S rRNA gene. Moreover, Chlamydia suis can become resistance to tetracyclines via mutations in the tet(C) gene. In addition, Chlamydia caviae may develop resistance to macrolides via variations in the 23S rRNA gene. The associated mechanisms of resistance are generally: the inhibition of bacteria's protein synthesis, the inhibition of bacterial enzymes' action and the inhibition of bacterial transcription process. Conclusion This literature review revealed the existence of diverse mutations associated with resistance to antibiotics using molecular tools and targeting chlamydia species' genes. Furthermore, these mutations were shown to be associated with different mechanisms that led to resistance. In that regards, more mutations and information can be shown by a deep investigation using the whole genome sequencing. Certainly, this can help improving to handle chlamydia infections and healthcare improvement by decreasing diseases complications and medical costs.